Giant pilomatrixoma on the back of neck: a unique case - Jha, Shruti; Singh, Jyoti; Kumar, Alekh; Singh, Rakesh K. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Pilomatrixomas are benign adnexal tumours, commonly occurring in the head and neck region. We present a unique case of giant pilomatrixoma on the posterior triangle of the neck, its diagnosis and subsequent treatment and its potential to become a primary differential diagnosis of slow-growing, benign masses. We report a case of 10×10 cm slow-growing painless mass in the nape of the neck with overlying ulcerations and conflicting radio-pathological pre-operative reports and its subsequent diagnosis as pilomatrixoma. Histopathological examination revealed the presence of ghost cells and basaloid cells, confirming the diagnosis. We stress the importance of recognizing this pilomatrixoma variant, whose clinical picture is confusing and obscure. We also reiterate the need for close follow up of small lesions due to the small but grave risk of malignant transformation and recurrence. Pilomatrixoma has variable presenting features and poses a diagnostic dilemma. Surgical planning can be done with the help of proper radiological features, and complete excision of the mass is required to achieve a cure.